Kingship, parliament and the court: the emergence of "high style" in petitions to the English crown, c.1350-1405 - Dodd, Gwilym (Oxford University Press, 2014)
In the second half of the fourteenth century, petitioners hoping to secure royal grace began addressing the king in an increasingly obsequious and ostentatious manner. A strong historiographical tradition is now established which regards this development in very narrow terms, as part of Richard II’s attempt to create a new type of authoritarian kingship in the late 1390s. Close analysis of the incidence of these new language forms shows, however, that they emerged much earlier in the fourteenth century. This discussion explores the reasons for this shift in language use, arguing that much broader political, cultural and institutional factors must be taken into account. The emergence of more elaborate ways of addressing the king is, in fact, of great consequence in revealing important developments in the nature of the fourteenth-century parliament, a dramatic shift in the culture of the royal court and, ultimately, a reconfiguration of the expectations of kingship itself. The discussion has at its heart an exploration of the way that language shaped and reflected political authority in the late Middle Ages.